Stapedotomy post-operative results and complications - S. Giri, Hanumant; C. Bishnoi, Ram; Nayak, Pooja D.; Gaikwad, Ninad S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Otosclerosis is a hereditary localized disease of the bone derived from the otic capsule. It is characterized by alternating phases of bone formation and resorption and patient presents with conductive hearing loss. Treatment of otosclerosis can be of two kinds: hearing aids and surgery. Stapedectomy and stapedotomy are the two surgical procedures done for treatment of otosclerosis. Present study was conducted on 30 patients with otosclerosis who underwent stapedotomy to assess the hearing results post-surgery by serial Audiometric studies and to study the complications of stapedotomy surgery. Methods: This prospective observational study conducted on 30 patients of otosclerosis who fulfilled the inclusion and exclusion criteria. Results: In this study of thirty cases of otosclerosis which were operated for small fenestra stapedotomy, we conclude that Hearing gain post-surgery was remarkable especially for patients with a pure conductive hearing loss. There was no deterioration in hearing after two years of follow-up. In our study on 30 patients we encountered minor complication in 4 patients (13.33%) and 1 major complication of profound sensorineural hearing loss 3.33%. Conclusions: We conclude that stapedotomy is a relatively safe procedure with significant post-surgery hearing benefit.